Recent, independent and anthropogenic origins of Trypanosoma cruzi hybrids. - Michael D Lewis; Martin S Llewellyn; Matthew Yeo; Nidia Acosta; Michael W Gaunt; Michael A Miles (Public Library of Science (PLoS), 2011)
The single celled eukaryote Trypanosoma cruzi, a parasite transmitted by numerous species of triatomine bug in the Americas, causes Chagas disease in humans. T. cruzi generally reproduces asexually and appears to have a clonal population structure. However, two of the six major circulating genetic lineages, TcV and TcVI, are TcII-TcIII inter-lineage hybrids that are frequently isolated from humans in regions where chronic Chagas disease is particularly severe. Nevertheless, a prevalent view is that hybridisation events in T. cruzi were evolutionarily ancient and that active recombination is of little epidemiological importance. We analysed genotypes of hybrid and non-hybrid T. cruzi strains for markers representing three distinct evolutionary rates: nuclear GPI sequences (n = 88), mitochondrial COII-ND1 sequences (n = 107) and 28 polymorphic microsatellite loci (n = 35). Using Maximum Likelihood and Bayesian phylogenetic approaches we dated key evolutionary events in the T. cruzi clade including the emergence of hybrid lineages TcV and TcVI, which we estimated to have occurred within the last 60,000 years. We also found evidence for recent genetic exchange between TcIII and TcIV and between TcI and TcIV. These findings show that evolution of novel recombinants remains a potential epidemiological risk. The clearly distinguishable microsatellite genotypes of TcV and TcVI were highly heterozygous and displayed minimal intra-lineage diversity indicative of even earlier origins than sequence-based estimates. Natural hybrid genotypes resembled typical meiotic F1 progeny, however, evidence for mitochondrial introgression, absence of haploid forms and previous experimental crosses indicate that sexual reproduction in T. cruzi may involve alternatives to canonical meiosis. Overall, the data support two independent hybridisation events between TcII and TcIII and a recent, rapid spread of the hybrid progeny in domestic transmission cycles concomitant with, or as a result of, disruption of natural transmission cycles by human activities.